Pengaruh Konverensi Lahan Sawit Terhadap Ketahanan Lingkungan di Kalimantan - Akhmad ZamZami; Muhammad Rhiswanda Immawan (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The widespread expansion of oil palm plantations on the island of Borneo has led to major changes in the conditions of existing landscapes and ecosystems. Tropical rainforests and peatlands that previously functioned as environmental buffers have been converted into oil palm monoculture plantations. This study aims to examine the impact of land conversion on various aspects of environmental resilience, especially related to hydrological functions, increased carbon emissions, and biodiversity sustainability. The method used in this study is Systematic Literature Review (SLR) by utilizing various secondary data derived from deforestation reports, hydrological research, and the latest scientific publications in the fields of ecology and environment. The results of the study show that the change in land use from forest to oil palm plantation results in a decrease in the soil's ability to absorb rainwater, thereby increasing surface flow and increasing the risk of seasonal flooding in downstream areas. In addition, the draining of peatlands through the construction of drainage systems and canals triggers the release of large amounts of carbon due to the oxidation process of organic matter stored in the peat. These conditions also increase vulnerability to forest and land fires that have an impact on environmental quality and climate change. On the other hand, massive land clearing causes habitat fragmentation which has an impact on declining biodiversity levels and isolating various endemic species, including the Bornean orangutan (Pongo pygmaeus), which is highly dependent on the existence of forests as their natural habitat.